ASSESSMENT OF INTEREST RATES INFLUENCE ON DEPOSIT MOBILISATION FOR SELECTED SAVINGS AND CREDIT CO-OPERATIVE SOCIETIES IN WESTERN KENYA. - LUVATE, GEOFREY; SANGORO, MR. OSCAR; MWAU, Dr. JONATHAN (IJRDO - Journal of Business Management, 2016)
From an institutional perspective, the primary motive for mobilizing savings lies in lower cost ofcapital compared to other sources of funds. In Western region, various cooperative societies havebeen registering losses and even some have gone out of business which has always been ascribedto reduced deposits by their customers. For instance, SACCOs such as Mumias Out growersSacco Society (MOSSACO) was temporarily closed down in 2009 because of depositswithdrawal by majority of its members thus leaving the SACCO with low capital base tofacilitate its operations. The interest rate at the time were at five percent while the one offered onloans were at 15 percent which were considered low on deposits and high on loans. The studydesign was a descriptive study with comparative design; the study population comprised ofemployees and customers of selected SACCOS. The study sample size was 293 members. Datacollection instruments were questionnaire and interview schedule. Reliability and validity ofinstrument were done accordingly. Data were analyzed by use of quantitative and qualitativemethods to determine the interest rates influence on deposit mobilization of the SACCOSselected for the study. It was found that most of the customers agreed that their knowledge oninterest rates has helped them to make savings in their respective SACCOs. This result suggeststhat trying to influence the SACCOs deposits by manipulating interest rates is not likely to be apractical policy option in western region. However it was recommended that the SACCOs shouldattempt to maintain competitive positive real interest rates relative to those offered by otherfinancial institutions in order to increase their savings. Further recommendation to use bothqualitative and inferential methods of analysis like liner correlations and Carrying out study withSACCOs that have member spread all over the country to refine the findings applicability